Balancing Roam Like At Home political objective with structural cost differences between domestic provision of mobile services - Laure Jaunaux; Philippe Deniau; Marc Lebourges (International Telecommunications Society (ITS), 2015)
This paper analyses the consequences on European markets of the introduction of “Roam Like At Home” (RLAH) obligation. Regulatory authorities have two main preoccupations when implementing RLAH obligation: the sustainability at retail level for home markets and the sustainability of RLAH at wholesale level for visited markets. We demonstrate that wholesale roaming regulation cannot be led by a roaming retail cost recovery principle as roaming retail services within RLAH obligation cannot be considered anymore as an autonomous economic activity. It is essential for regulation to ensure that roaming providers are able to recover full costs of providing wholesale roaming services. However, wholesale roaming regulation can be justified only if the market is not competitive. Competitive wholesale roaming markets would not erase the heterogeneity of mobile service provisions costs between European Member States, which implies that either some national mobile market may be subject to increase of domestic price or to depart from pure RLAH and allow RLAH+, that is a limited charge on top of domestic price, above a given level of roaming usages.
Keywords: 330